Migrant-friendly maternity care in Montreal, Canada: A cross-sectional study on migrant women’s care perspectives - Isabel Baltzan; Lisa Merry; William Fraser; Sonia Semenic; Sandra Pelaez; Alexis Edington; Ayesha Baig; Anita Gagnon (PLoS ONE, 2025)
Objective We assessed the extent to which recommended migrant-friendly maternity care (MFMC) components were provided to recently-arrived international migrants giving birth in Montreal, Canada, and the extent to which the provision of MFMC components was related to socioeconomic and migratory characteristics. Methods We conducted a cross-sectional study of migrant women giving birth in four hospitals in 2014–2015. Data were collected using the Migrant-Friendly Maternity Care Questionnaire (MFMCQ), focusing on access to prenatal care, communication facilitation, healthcare provider (HCP) support, and responsiveness to preferences for care. Data were analyzed descriptively and through logistic regression. Results Of 2636 participants, most reported always being kept informed (86.1%) and finding HCPs helpful (90.3%), although 22.9% reported barriers to accessing services during pregnancy, and only 11% or less were asked about care preferences. Of 847 needing interpreters, 84.7% reported not being offered any. Worse access to prenatal care was reported among women who had arrived more recently [OR 0.55, 95% CI 0.36, 0.85], had lower income [0.69 (0.52, 0.90)], or had less education [0.66 (0.47, 0.94)]. Low language ability was most often associated with inadequate MFMC [e.g., worse HCP support during pregnancy [0.56 (0.36, 0.87)] and worse responsiveness to preferences for care during labour [0.55 (0.31, 0.98)]]. Maternal region of birth was associated both positively and negatively with all MFMC components. Conclusion Although some MFMC has been implemented, gaps remain. Addressing language barriers remains a top priority. To deliver optimal MFMC, HCPs and policymakers should provide care that is responsive to women’s socioeconomic and migratory backgrounds.